Study on the burden of digestive diseases among Chinese residents in the 21st century - Gong, Shijun; Zhang, Yuyu; Wang, Yaqiong; Yang, Xianhu; Cheng, Baolian; Song, Ziyi; Liu, Xingrong (Frontiers in Public Health, 2024)
Background The global burden of digestive diseases has increased in recent years. The study aims to comprehend the trend of incidence and death rates related to digestive diseases in China from 2000 to 2020. Methods The study collected data on digestive diseases and their causes, such as incidence rates, death rates, Years of Life Lost, Years Lived with Disability, Disability-Adjusted Life Years and estimated annual percentage change from the 2019 Global Burden of Disease website and the Chinese Health and Wellness Statistical Yearbook spanning. And we employed the age-period-cohort model to analyze the influence of age, period, and birth cohort on the trend of death rates associated with digestive diseases. Results In contrast to the global burden of digestive disease, China experienced increases in the age-standardized incidence for inflammatory bowel disease, gallbladder and biliary diseases, as well as appendicitis from 2000 to 2019. The corresponding estimated annual percentage change for these diseases were 2.06, 1.74, and 0.99. Females showed a significantly higher incidence of digestive diseases, while males experienced a higher death rate. Moreover, individuals in the age groups under 5 years and over 60 years exhibited higher death rates than those in other age groups. Conclusion The findings underscore the ongoing importance of digestive diseases as a substantial public health issue in China. Reducing the disease burden of IBD in China necessitates healthcare systems to enhance their infrastructure and personnel readiness, ensuring an equitable, affordable, and accessible distribution of care for IBD patients. To reduce the occurrence and mortality rates of digestive diseases in China, the government should promote the adoption of early screening policies for individuals under the 5 year and those above the 60 year. These policies should be accompanied by customized preventive measures.